2010
DOI: 10.1136/vr.b4763
|View full text |Cite
|
Sign up to set email alerts
|

Infectious canine hepatitis in red foxes (Vulpes vulpes) in the United Kingdom

Abstract: The pathological findings are described in three cases of infectious canine hepatitis in free-ranging red foxes (Vulpes vulpes) in England. The foxes died after short periods of clinical illness. Mild jaundice and hepatic congestion were evident grossly. On histopathological examination, intranuclear inclusion bodies were visible in hepatocytes, in association with hepatocyte dissociation and necrosis, as well as in renal glomeruli, renal tubular epithelial cells and vascular endothelial cells. Canine adenovir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 21 publications
(37 reference statements)
0
30
1
Order By: Relevance
“…The availability of a dog cell line of hepatic origin permitted us to enrich the viral load of the samples analyzed, and to reduce background sequence information of the host. Although CAV-1 viruses are cultured generally on Madin Darby Canine Kidney cells (Thompson et al, 2010;Decaro et al, 2008), this study shows that canine BDE cells are also suitable for viral amplification. After three inoculations, a distinctive cytopathogenic effect, including grape-like cell clusters typical of CAV-1 (Decaro et al, 2008), was observed.…”
Section: Adaptermentioning
confidence: 84%
See 1 more Smart Citation
“…The availability of a dog cell line of hepatic origin permitted us to enrich the viral load of the samples analyzed, and to reduce background sequence information of the host. Although CAV-1 viruses are cultured generally on Madin Darby Canine Kidney cells (Thompson et al, 2010;Decaro et al, 2008), this study shows that canine BDE cells are also suitable for viral amplification. After three inoculations, a distinctive cytopathogenic effect, including grape-like cell clusters typical of CAV-1 (Decaro et al, 2008), was observed.…”
Section: Adaptermentioning
confidence: 84%
“…Furthermore, this fouryear-old dog acquired the CAV-1 infection at a relatively old age, whereas hepatitis contagiosa canis occurs mainly in more susceptible younger dogs and is characterized by severe necrosis and many viral nuclear inclusions (Decaro et al, 2008). Due to vaccination strategies hepatitis caused by CAV-1 had disappeared almost completely, however, in Europe, CAV-1 is re-emerging and outbreaks of the disease have been reported in unvaccinated dogs and foxes (Thompson et al, 2010;Decaro et al, 2007). The dog in this study did not receive all the recommended vaccinations and remained therefore susceptible for CAV-1 infection.…”
Section: Adaptermentioning
confidence: 94%
“…Infectious canine hepatitis is nowadays considered a neglected canine disease and veterinary practitioners rarely take into account CAdV-1 as causative agent of disease. Nevertheless, cases of ICH and of asymptomatic CAdV-1 infections have been documented in recent years in foxes and dogs (Balboni et al, 2013(Balboni et al, , 2014Caudell et al, 2005;Decaro et al, 2007;Headley et al, 2013;Müller et al, 2010;Pratelli et al, 2001;Thompson et al, 2010), confirming that the CAdV-1 continues to circulate and to be pathogenic in dogs. Furthermore, CAdV types are detectable in the same biological matrices (Balboni et al, 2013(Balboni et al, , 2014Decaro et al, 2004;Greene, 2012) and viral coinfection with CAdV-1 and CAdV-2 are detectable with high frequency (Balboni et al, 2013(Balboni et al, , 2014Headley et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…However, the pathology and clinical signs of ICH in naturally infected, free-ranging canids are not well characterised. Red foxes in the UK (Thompson and others 2010) and Italy (Balboni and others 2013) appear to be a wildlife reservoir of CAV-1. Serological exposure to untyped CAV in several free-ranging carnivore species has been reported worldwide (Amundson and Yuill 1981, Truyen and others 1998, Thompson and others 2010), suggesting that CAV-1 may be sustained in wild canid populations.…”
Section: Introductionmentioning
confidence: 99%
“…Red foxes in the UK (Thompson and others 2010) and Italy (Balboni and others 2013) appear to be a wildlife reservoir of CAV-1. Serological exposure to untyped CAV in several free-ranging carnivore species has been reported worldwide (Amundson and Yuill 1981, Truyen and others 1998, Thompson and others 2010), suggesting that CAV-1 may be sustained in wild canid populations. However, there are only a few reports of the occurrence of spontaneous ICH in free-ranging foxes (Woods 2001), limited to descriptions of isolated cases in a grey fox ( Urocyon cinereoargenteus ) (Gerhold and others 2007) and three red foxes (Thompson and others 2010).…”
Section: Introductionmentioning
confidence: 99%